The effect of synbiotics supplement on alcohol use disorders identification test and biochemical parameters, lipopolysaccharide and immunoglobulin a levels, in high risk alcoholics - Vachrintr Sirisapsombat (2020)
© 2019 IEEE. To investigate the possible effects of synbiotic supplement affecting to gut-liver-brain axis in high risk alcohol drinkers through alterations between improving of gut related parameters and changes of event related potentials on tasks. Design: Single group, pre- and post-test study. Participants: 24 male patients, alcohol use disorders identification test (AUDIT) at 8 or above. Exclusions included clinical diagnosis of cirrhosis, immunodeficiency, autoimmune disorder, use of drugs other than alcohol, pregnancy and lactation, use of antibiotics and herbs during the course of study. Intervention: Synbiotic containing probiotic 7 species and prebiotic 3 types once a day before bedtime for 8 weeks. Main outcome measures: Primary outcome- the efficacy of synbiotics supplement improving subjective AUDIT score. Secondary outcome- changes on gut related biochemical parameters (lipopolysaccharide and immunoglobulin A levels). Result: twenty high risk alcoholic subjects (with an average age of 46.14 ± 18.34 years) were supplemented with synbiotics contained 25 billion cells of probiotic per day for 8 weeks. After the end of intervention, there was significantly improved total AUDIT scores (p =0.001). The changes in lipopolysaccharide and immunoglobulin A level was calculated. Both lipopolysaccharide (from 23.19 ± 9.57 to 16.67 ± 4.52 mg/ml) and immunoglobulin A (from 377.13 ± 229.88 to 484.16 ± 290.98 ng/ml) levels were significantly changed when compared to the baseline value. The results of the current study suggested that the consumption of synbiotics significantly improved subjective and objective parameters in high risk alcoholic patients, and further studies are mandatory to reveal the effects of synbiotics on gut health link to central neurological system.